The Effects of Industry-Level Uncertainty on Cash Holdings: The Case of Germany - Christopher F. Baum; Dorothea Schäfer; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper investigates the link between the optimal level of non-financial firms' liquid assets and industry-level uncertainty. We develop a structural model of a firm's value maximization problem that predicts that as industry-level uncertainty increases the firm will increase its optimal level of liquidity. We test this hypothesis using a panel of German firms drawn from the Bundesbank's balance sheet database and show that greater uncertainty at the industry level causes firms to increase their cash holdings. The strength of these effects differ among subsamples of the firms with different characteristics.
Keywords: L14; G31; G32; 330; Uncertainty; cash holdings; liquidity; non-financial firms; Betriebliche Liquidität; Unternehmenswert; Verarbeitendes Gewerbe; Schätzung; Deutschland